احمد حسن الخفاجي دراسة التلوث البكتيري المصاحب للحروق الجلدية وبيان مدى استجابة للمضادات الحيوية - احمد حسن (University of Thi-Qar Journal of Science, 2019)
The infection that related with burns usually cause many of health problems due to destruction of the skin tissues thatconsidered the largest part of human body that protect body from external factors in addition to the suppression of immunity in thesite of burn, so the aim of this study is to define the causative agents of microbial burn contamination and concern theantibiotics against it. Isolation of bacteria had been doing by make skin swaps from burn site to 54 patient and inoculated to different culture media  like nutrient broth, blood agar and MacConkey agar. The results appeared that 77.7% of samples were positive to the bacterial culture and there were two species of bacteria in this studyresponsible of the bacterial infection of the burns, they werePseudomonas aeruginosa and Staphylococcus aureus with 66.6%and 33.3% of isolation respectively.In the other hand, two antibiotics work efficiently on P. aeruginosa and they were Gentamicin and Ciprofloxacin, while each of Amoxiclave, Ciprofloxacin and Tetracycline are act effectively on S. aureus.